(untitled) (Bangladesh Pharmaceutical Journal, 2026)
Annona muricata L. is a small-evergreen tree with potential pharmacological applications in traditional medicine. Here, the methanolic extract of A. muricata leaf was subjected to phytochemical and biological assays. During preliminary phytochemical screening, alkaloid, flavonoid, steroid, glycoside, phenol, carbohydrate and tannin were discovered revealing the plant’s rich chemical composition. It exhibited strong antioxidant activity which was evident from DPPH radical quenching assay with an IC₅₀ of 30.95 µg/ml. The extractive also presented a significant total phenolic content (63.74 mg GAE/g). In an oral glucose tolerance model in mice, the leaf extract of A. muricata at the dose of 400 mg/kg revealed a marked and dose-dependent reduction in blood glucose levels, demonstrating a comparable efficacy to standard glibenclamide. These findings suggest that synergistic phytoconstituents in A. muricata may modulate oxidative stress and glucose homeostasis, supporting its development as a promising natural agent for antidiabetic intervention. Bangladesh Pharmaceutical Journal 29(1): 93-98, 2026 (January)